PENGARUH LATIHAN TARGET TERHADAP KETEPATAN PUKULAN GYAKU-TSUKI PESERTA DIDIK EKSTRAKURIKULER KARATE - Ferdi Fahrorazi; Victor G Simanjuntak; Eka Supriatna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem in this research is that there are karate extracurricular activities in SMP Tahfizul Qur'an Pontianak.The accuracy of the gyaku-tsuki punches of the students is not good. This study aims to determine the effect of target training on the accuracy of the gyaku-tsuki punch of karate extracurricular students in SMP Tahfizul Qur'an Pontianak. The method used in this study is an experiment with a form of pre-experimental research and research models using one group pretest-posttest design models. The data source of this study were students who participated in karate extracurricular activities at the SMP Tahfizul Qur'an Pontianak with a sample of 21 people. Data analysis using t test (paired sample t test) at the significance level of 0.05. Based on the analysis of data and the results of research that has been done, it can be concluded that there is the effect of target training on the accuracy of the gyaku-tsuki punch of karate extracurricular students in SMP Tahfizul Qur'an Pontianak, with a value of 9.975: a pretest value of the number of 21 participants achieved an average of 4.76. Posttest value of 21 participants achieved an average value of 7.38. With a percentage increase of 55.25%. Keywords: Target Practice, Accuracy, Gyaku-Tsuki Punch